A Rare Case of Neonatal Birth with Congenital Bilateral Femoral Deficiency Undetected in Prenatal Ultrasound - Somayeh Makvandi; Maryam Kolahkaj (Mashhad University of Medical Sciences, 2019)
Background:Prenatal ultrasound plays an important role in the early and accurate evaluation of the congenital skeletal and non-skeletal abnormalities of the fetus and is effective in predicting pregnancy outcomes. Congenital femoral deficiency (CFD) is a rare complicated and non-hereditary anomaly that includes the hypoplasia of a portion of the femoral bone with shortening the lower limb. Case report: The aim of this study was to report a rare case of neonatal CFD, which was not detected in prenatal ultrasound. In this study, we presented the case of a 28-year-old multiparous woman with the gestational age of 39 weeks hospitalized for labor pain. She had a history of 2 to 3 irregular prenatal visits and her only pregnancy ultrasound was related to late pregnancy, which reported a healthy live fetus with a cephalic presentation, which was in 35-36 weeks of gestation according to biparietal diameter (BPD) and femur length (FL). Finally, normal vaginal delivery occurred and a neonate was born with a severe bilateral CFD with deformity and immobilization of the lower limbs. Conclusion: It seems that in order to identify the early diagnosis and case management it is necessary to differentiate both femoral and tibia bones in routine ultrasound more precisely, measure the length, and strongly emphasize the need for the ultrasound examination of fetal anomalies for all pregnant women.